2022
DOI: 10.1039/d2ja00182a
|View full text |Cite
|
Sign up to set email alerts
|

A transferred multitask regularization convolutional neural network (TrMR-CNN) for laser-induced breakdown spectroscopy quantitative analysis

Abstract: Laser-induced breakdown spectroscopy (LIBS) combined with machine learning has demonstrated great capabilities for quantitative elemental analysis. When the distributions of training and test data differ due to changes in measurement...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Davari et al [82] fused the Lasso model with a one-dimensional CNN method to analyze LIBS spectra of single-crystal silicon and measured the oxygen-related impurities in the samples with LOD as low as 0-16 ppm. Cui et al [83] proposed a migration-learning multitask regularized CNN model for quantitative analysis of coal samples on a dataset with small sample size. Compared with PLS, SVM regression, and ordinary CNN networks, the RMSE of this method was reduced by 19.9%, 5.9%, and 7.7%, respectively.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Davari et al [82] fused the Lasso model with a one-dimensional CNN method to analyze LIBS spectra of single-crystal silicon and measured the oxygen-related impurities in the samples with LOD as low as 0-16 ppm. Cui et al [83] proposed a migration-learning multitask regularized CNN model for quantitative analysis of coal samples on a dataset with small sample size. Compared with PLS, SVM regression, and ordinary CNN networks, the RMSE of this method was reduced by 19.9%, 5.9%, and 7.7%, respectively.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…The techniques establish connections between source and target domains that have different but related distributions and can share features between domains. Cui et al 15 proposed a transfer learning method called transferred multitask regularization convolutional neural network (TrMR-CNN) to address the small-sample problem in LIBS quantification analysis and improve the generalization ability of transfer learning. Compared with other machine learning methods, TrMR-CNN with high accuracy has great power in LIBS quantification analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16] used wavelet neural network (WNN) to classify coal ash, and the results showed that WNN showed better classification performance. Cui et al [17] used CNN, combined with multi-task regularization, proposed a transfer learning method which significantly reduced the RMSEP compared with the baseline method. Chen et al [18] proposed a moisture-spectral intensity correction model, and established an ANN model to improve the model prediction capability.…”
Section: Introductionmentioning
confidence: 99%